Spontaneous fluctuation in atrial fibrillation burden and duration in patients with implantable loop monitors - Mekary, Wissam; Campbell, Martin; Bhatia, Neal K.; Westerman, Stacy; Shah, Anand; Leal, Miguel; Delurgio, David; Patel, Anshul M.; Tompkins, Christine; El‐Chami, Mikhael F.; Merchant, Faisal M. (Pacing and clinical electrophysiology, 2024)
Background Most studies of device‐detected atrial fibrillation (AF) have recommended indefinite anticoagulation once a patient crosses a particular threshold for AF duration or burden. However, durations and burdens are known to fluctuate over time, but little is known about the magnitude of spontaneous fluctuations and the potential impact on anticoagulation decisions. Objective To quantify spontaneous fluctuations in AF duration and burden in patients with implantable loop recorders (ILRs) Methods We reviewed all ILR interrogations for patients with non‐permanent AF at our institution from 2018 to 2023. We excluded patients treated with rhythm control. The duration of longest AF episode at each interrogation was classified as < 6, 6–24, and > 24 h, and the AF burden reported at each interrogation was classified as < 2%, 2%–11.4%, and > 11.4%. Results Out of 156 patients, the mean age at ILR implant was 70.9 ± 12.5 years, CHA2DS2‐VASc score was 4.2 ± 1.8, duration of ILR follow‐up was 23.4 ± 11.2 months, and number of ILR interrogations per patient was 18.0 ± 8.9. The duration of longest AF episode at any point during follow‐up was < 6 , 6–24 , and > 24 h in 110, 30, and 16 patients, respectively. Among the 30 patients with a longest AF episode of 6–24 h at some point during follow‐up, out of 594 total ILR interrogations, only 75 (12%) showed a longest episode of 6–24 h. In the remaining 519 interrogations, the longest episode was < 6 h. In patients with a longest episode of > 24 h at any point during follow‐up (n = 16), only 47 out of 320 total ILR interrogations (15%) showed an episode of > 24 h. When evaluating AF burden, 96, 38, and 22 patients had maximum reported AF burdens of < 2%, 2%–11.4%, and > 11.4% at any point during ILR follow‐up. Among those with a maximum burden of 2%–11.4% at some point during follow‐up (n = 38), out of 707 ILR interrogations, only 76 (11%) showed a burden of 2%–11.4%. In the remaining 631 interrogations, the burden was < 2%. In the 22 patients with a burden > 11.4% at some point during follow‐up, only 80 out of 480 interrogations (17%) showed a burden of > 11.4%. In 65% of interrogations, the burden was < 2%. Conclusion Significant, spontaneous fluctuations in AF burden and duration are common in patients with ILRs. Even in patients with AF episodes of 6–24 h or > 24 h at some point during follow‐up, the vast majority of interrogations show episodes of < 6 h. Similarly, in patients with burdens of 2%–11.4% or > 11.4% at some point during follow‐up, the vast majority of interrogations show burdens of < 2%. More data are needed to determine whether crossing an AF burden or duration threshold once is sufficient to merit lifelong anticoagulation or whether spontaneous fluctuations in AF burden and duration should impact anticoagulation decisions.